’Quéresme facer o favor de calar?’: Basics for a Communicative Grammar for the Galician Language - Bravo García, Ana; López Iglesias, Nerea (Madrygal. Revista de Estudios Gallegos, 2019)
The study of communicative functions is essential for language learning. In the past few years, a very fruitful line of work, whose main aim is to elaborate communicative grammars and their didactic application, has been developed. However, there is no reference work such as this in the Galician language. For that reason, this paper’s aim is to propose a series of fundamental parameters for the elaboration of a work of this nature, based on the description of the functions of request and order from a communicative point of view. It will also pay attention to the possible didactic applications that these grammars should have, so that they can be a more useful tool for both teachers and students.